Game Edukasi 2d Pengenalan Silsilah Keluarga Berdasarkan Suku Berbasis Android - Ridho Parmonangan Manurung; Anggy Trisnadoli (Politeknik Caltex Riau, 2021)
In the current era of globalization, children's lack of knowledge about family tree is quite high. A total of 30 children can only answer an average of 30 percent of the 10 questions about family tree. This is influenced by the high level of urbanization, lack of introduction to family tree by parents, modern urban environment and less interactive book learning media. So we need an alternative learning media for children to introduce family tree based on ethnicity in addition to using books, with educational games. It is hoped that the games made can be an alternative learning media apart from reading books. The game is made in the form of a puzzle piece of family members' pictures. From the results of the media expert validation test using the LORI (Learning Object Review Instrument) standard, the percentage value is 87% and is classified as very good. From the results of the material expert validation test using the LORI standard, the percentage obtained is 94% and is classified as very good. From the results of testing and data analysis on the pre-test and post-test scores using the Paired Sample t-Test, there are significant differences in the values ​​of the pre-test and post-test. From the results of the N-gain Score test, the percentage value is 62.10% and is considered quite effective. It can be concluded that the 2D educational game introducing the family tree based on the built tribe can be used as an alternative learning media besides books to introduce the family tree to children.